Fracture Identification of Deep Dolomite Reservoir Based on R/S-FD Analysis: A Case Study of the Cambrian Sinian Reservoirs in the Sandaoqiao Gas Field, Northern Tarim Basin - Meng, Qingxiu; Ding, Wenlong; Diao, Xindong; Han, Pengyuan; Wang, Huanhuan; Xiao, Zikang (Frontiers in Earth Science, 2022)
The pre-Mesozoic Sandaoqiao gas field, northern Tarim Basin, Western China, hosts a typical deep fractured dolomite reservoir. Taking this area as an example, this study carried out identification research on the fracture development section of the Cambrian Sinian deep (5700m-6200m) thick (60m-80m) fractured dolomite reservoirs. The core scale identification and numerical analysis method of heavy gauge finite difference (R/S-FD) are used to identify the fracture development section. In the process of applying this method to the study area, by comparing the fracture development identification results of continuous and complete coring sections, three logging curves with high fracture sensitivity (AC / DEN/ CAL) are selected. The adjusted R/S-FD analysis method can effectively identify the fracture development section of fractured dolomite reservoir. Among them, five fracture development sections were identified in well Q1, with an average thickness of 6.8m. The fracture development section is in good consistency with the reservoir interpretation section of conventional logging. Well Q101 identified 11 fracture development sections with an average thickness of 2.5m. The results show that the gas logging section lags behind the fracture development section, mainly corresponding to the lower part of the identified fracture development section. The thickness and distribution of the longitudinal fracture development section of the two wells are obviously different. The research shows that R/S-FD method can well identify the fracture development section of fractured dolomite reservoir.